2019
DOI: 10.5812/mca.87711
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Relationship Between Serum Uric Blood Levels and the Severity of Coronary Artery Disease in Angiography of Patients with Acute Coronary Syndrome

Abstract: Background: Uric acid as an inflammatory marker has been hypothesized as a precursor of atherosclerosis and its role has been evaluated in recent studies. Objectives: In our study we wanted to assess its effect on the severity and extent of coronary artery disease in patients presenting to emergency department with acute coronary syndrome. Methods: In this cross-sectional descriptive study, we enrolled all patients with ACS who attended to Shahid Rajaie Emergency Department from May 2016 to May 2018. All patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…11 Another concluded that measuring SUA levels in patients presenting with acute coronary syndrome could help determine the patient's general probability of atherosclerotic disease and is both sensitive and efficient. 12 Moreover, assessing SUA levels in addition to traditional risk variables in routine clinical practice may offer important predictive advantages in terms of assessing overall cardiovascular risk and managing patients. 13,14 However, the study aimed to determine the association between SUA levels and the angiographic severity of CAD.…”
Section: Introductionmentioning
confidence: 99%
“…11 Another concluded that measuring SUA levels in patients presenting with acute coronary syndrome could help determine the patient's general probability of atherosclerotic disease and is both sensitive and efficient. 12 Moreover, assessing SUA levels in addition to traditional risk variables in routine clinical practice may offer important predictive advantages in terms of assessing overall cardiovascular risk and managing patients. 13,14 However, the study aimed to determine the association between SUA levels and the angiographic severity of CAD.…”
Section: Introductionmentioning
confidence: 99%